THE RELATIONSHIP BETWEEN THE EFFECTIVENESS OF INTERNAL CONTROL SYSTEMS AND THE QUALITY OF FINANCIAL REPORTS IN IRAQI COMMERCIAL BANKS - Abbas Fadel Chiyad (Scholars Digest Publishing, 2025)
This study aimed to evaluate the effectiveness and efficiency of internal control systems and their impact on the quality of financial reports and statements in financial institutions operating in the Iraqi Stock Exchange, and to shed light on the set of control procedures and means, whether accounting or administrative, on which these institutions depend and the extent of their impact on the fairness and accuracy of financial reports, The researcher used the descriptive approach by using the questionnaire as a basic tool in the study community consisting of all Iraqi financial institutions and commercial banks. A group of these financial institutions were selected through a random sample represented by financial and administrative managers, internal auditors, auditors, chartered accountants, and members of the Audit and Monitoring Profession Council and the Financial Control Bureau, The researcher used a questionnaire for the purpose of achieving the research objective consisting of (10) paragraphs to collect basic information about the research sample and analyze it using the statistical program (SPSS) to achieve the research objectives and then reach the conclusions and recommendations of the study that were extracted from the theoretical and practical aspects, The study concluded the importance and role of internal control systems in raising the efficiency and performance of financial institutions and protecting their cash and non-cash assets. The study recommended the need to pay attention to the scientific qualification, professional competence and practical experience of internal auditors.
Keywords: Internal control, efficiency and effectiveness, financial reporting, commercial banks, accounting information, internal auditors, Internal adjustment device.